Evaluasi dan Perbaikan Proses Bisnis dengan Quality Evaluation Framework (QEF), Root Cause Analysis (RCA), dan Teknik Esia (Studi Kasus: Pelayanan Pasien BPJS Rawat Jalan Rumah Sakit Islam Aisyiyah Malang) - Tirta Saraswati; Ismiarta Aknuranda; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Islam Aisyiyah Hospital Malang is the one of private hospitals that acccepted inpatient and outpatient BPJS services. The business process of outpatient BPJS patient services Islam Aisyiyah Hospital is a service for BPJS patients by providing examinations and medication in one day without hospitalization. The BPJS outpatient services can be done in two ways, through the UGD if the patient condition emergency and through the Polispesialis if the patient is referral from a clinic or health centre. During the implementation of the BPJS outpatient services there were still problems about the detection of the referral number, the poly destination, and the patient's hospital destination in the referral letter at BPJS application and the patient's file was exchanged during the registration process. Based on these problems, it is necessary to evaluate business processes using Quality Evaluation Framework (QEF) to knows the suitability of achieving the company's by the business processes that have been modeled using Business Process Modeling and Notation (BPMN). The next step is to find the root problems with Fishbone Analysis. After that, the next step is to improve business processes using ESIA techniques (Eliminate, Simplify, Integrate, and Automation). And then, the results of business process simulation the outpatient services of BPJS at Polispesialis increased by 16.69% and at the UGD the Islam Aisyiyah Hospital increased by 4.01%.